Role and management of permanent grasslands - Sabanci C.O. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Permanent grasslands are open areas covering nearly one fourth of the total land area in the world. Temperate grasslands such as prairies, pampas, steppes or paramos have hot and dry summers, and rainy cool winters. Grasslands are vitally important for livestock as a feed source, environmental protection, conservation of genetic resources, preservation of natural resources, sustainable agriculture, wildlife habitat, tourism and leisure. As a science and technique, the grassland management provides the maximum production with the conservation of vegetation, soil and the other natural resources. The effective management of grasslands depends on a number of different factors such as the characteristics of grassland, plant species, livestock type and environmental sources. Use of proper grazing system is the most important practice in management. The main principles of grazing management are grazing capacity in relation to the number and kind of animals, grazing period and grazing distribution. Grassland management also involves weed control, fertilization, burning, and seeding with natural grasses or other plants.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)